The Social Ties that Bind: Unraveling the Role of Trust in International Intelligence Cooperation. Issue 2 (3rd April 2023) - Tuinier, Pepijn; Zaalberg, Thijs Brocades; Rietjens, Sebastiaan
Abstract: International cooperation between intelligence services poses a dilemma. It is an important tool in countering today's complex transnational threats, but at the same time, cooperation is a risky business. Intelligence services can never be sure that a partner will reciprocate in kind. Scholars and practitioners often identify trust as one of the foremost conditions to overcome this dilemma. Yet the notion of trust is seldomly conceptualized in these rational-calculative explanations. Contrary to the common view that intelligence services are exceptional in their opportunism and rivalry, social relations and trustworthiness perceptions provide a more dominant explanation for the level of cooperation between intelligence partners than is often assumed by scholars and practitioners. Known reputations, recognized professional standards, and shared traits socially bind intelligence professionals to their community of practice, enabling them to bridge divides like nationality and even conflicting interests. Intelligence services resemble many other organizations in the public and private domains, requiring a de-exceptionalization of their international cooperation.